2009
DOI: 10.1111/j.1749-6632.2009.04458.x
|View full text |Cite
|
Sign up to set email alerts
|

The Compensatory Growth in Juveniles of Sea Bass

Abstract: The aim of this work was to investigate the distribution of regulative molecules in the stomach of juvenile Dicentrarchus labrax during compensatory growth, using immunohistochemical methods. Antisera against galanin, neuropeptide Y, ghrelin, leptin, and serotonin were used on fasted and refed D. labrax. The results show a characteristic distributive pattern for the sought molecules in fish refed after 35 days of fasting, with a high increased presence of both ghrelin and leptin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Our data show that serotonin presence and distribution in the stomach of adult P. antarcticum is similar to that generally observed in temperate perciformes (Radaelli et al 2001;Ferrando et al 2009). …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our data show that serotonin presence and distribution in the stomach of adult P. antarcticum is similar to that generally observed in temperate perciformes (Radaelli et al 2001;Ferrando et al 2009). …”
Section: Discussionsupporting
confidence: 84%
“…Negative control included the omission of the primary antiserum. Positive control was performed on the stomach of Dicentrarchus labrax (Ferrando et al 2009). …”
Section: Histological and Immunohistochemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings that G αtran immunoreactivity was localized to distinct subsets of EECs expand previous data in other animals species (Rozengurt et al 2006; Sutherland et al 2007; Moran et al 2010; Janssen et al 2011, Steinert et al 2011; Mazzoni et al 2013). EECs have been reported in the stomach and intestine of several fish species (Holmgren et al 1982; Reinecke et al 1997; Ku et al 2004; Bermúdez et al 2007; Manning et al 2008), including the sea bass, where 5-HT-, SOM- and GHR-IR EECs have been described (Visus et al 1996; Ferrando et al 2009a; Terova et al 2008). Our study has shown GHR-IR cells in the gastric mucosa, many of which contain G αtran -IR.…”
Section: Discussionmentioning
confidence: 99%
“…A CG response has been reported in salmonids (Dobson and Holmes, 1984; Jobling et al, 1993; Maclean and Metcalfe, 2001; Nikki et al, 2004), cyprinids (Russell and Wootton, 1992; Wieser et al, 1992), perciformes (Hayward et al, 1997; Picha et al, 2006, 2008b; Turano et al, 2007, 2008; Ferrando et al, 2009), flatfish (Cho, 2005; Heide et al, 2006), sticklebacks (Zhu et al, 2003), cichlids (Wang et al, 2000), catfish (Gaylord and Gatlin, 2000), and gadids (Jobling et al, 1994). While the degree of growth compensation achieved depends on species, it is nonetheless typically characterized by hyperphagia, improved feed conversion efficiency, and elevated specific growth rate (SGR).…”
Section: Introduction: Compensatory Growth Overviewmentioning
confidence: 93%